مستوى الاستيعاب القرائي باللغة العربية لدى طلبة الصف العاشر الأساسي في فلسطين - مصلح، عمران احمد علي
This study aims to identify the level of reading comprehension in Arabic of tenth grade students in the province of Ramallah and Al-Bireh Palestine, and subsequently identify the effect of some of the independent variables on the comprehension level of these students. In order to achieve the goal of the study, the researcher set up a test measuring the level of the reading comprehension competence in twelve skills important to students, included in the curriculum of Arabic for the tenth grade. The study's stratified sample of (٥٠٥) students was selected randomly from (١٩) different schools, at a rate of (١٠.٢٦%) of the study's original mixed-gender population that is (٤٩٢٣) students. The results of the study showed that the level of reading comprehension of the students had varying degrees; whereby the degree of response in the skill: (identify the details contained in the text) scored very low with a response rate of (٤٩%). The response rate was also low in three other skills that are: (understand the meaning of a word or phrase in the context, choose an appropriate title, and find the general idea). The level of response was average in six skills: (specify the noun to which the pronoun refers, determine the writer's intent and purpose, make out cause-and-effect relationships, determine the degree of benefit from the text, and identify the metaphorical meaning in sentences). Two skills: (identify the topic of the text, and discern sentences that trigger emotions) scored high. The skill with a very high score of responsiveness was: (figuring out the character's traits and features), which attained (٨٠%). Findings also revealed that female respondents did better than male. Furthermore, the study showed the existence of significant differences in the level of reading comprehension linked to the level of attainment in Arabic, the number of hours spent on reading, leisure weekly reading, and the academic qualifications of the parents. In addition, the results noted the superiority of students in private schools over those in public ones and of city or village students over camp students. Finally, the results revealed the high level of reading comprehension among students of the literary text compared with the scientific text.